Characterizing initiation, use, and discontinuation of extended-release buprenorphine in a nationally representative United States commercially insured cohort. (1st August 2021) - Morgan, Jake R.; Walley, Alexander Y.; Murphy, Sean M.; Chatterjee, Avik; Hadland, Scott E.; Barocas, Joshua; Linas, Benjamin P.; Assoumou, Sabrina A.
Highlights: Studied 204 early adopters of injectable buprenorphine compared to other medications. Discontinuation is common across opioid use disorder medications. No evidence that injectable buprenorphine offered a retention advantage. Good concordance with injectable buprenorphine prescribing guidelines. Abstract: Background and Aims: While the United States is in the midst of an overdose epidemic, effective treatments are underutilized and commonly discontinued. Innovations in medication delivery, including an extended-release formulations, have the potential to improve treatment access and reduce discontinuation. We sought to assess extended-release buprenorphine discontinuation among individuals with opioid use disorder (OUD) in a real-world, nationally representative cohort. Setting: United States Participants: Commercially insured individuals initiating one of four FDA-approved medications for opioid use disorder (MOUD) in 2018: extended-release buprenorphine, extended-release naltrexone, mucosal buprenorphine (mono- or co-formulated with naloxone), or methadone. Measurements: Our primary outcome was medication discontinuation, defined as a gap of more than 14 days between the end of one prescription or administration and the subsequent dose. Findings: We identified 14, 358 individuals initiating MOUD in 2018, including 204 (1%) extended-release buprenorphine, 1, 173 (8%) extended-release naltrexone, 12, 171 (85%) mucosal buprenorphine, and 810 (6%) methadone initiations. Three months after initiation, 50% (95% confidence interval [CI] 40%-60%) of extended-release buprenorphine, 64% (95% CI 61%-69%) of extended-release naltrexone, 34% (95% CI 33%-35%) of mucosal buprenorphine, and 58% (95% CI 54%-62%) of methadone initiators had discontinued treatment. Conclusions: Across all treatment groups, medication discontinuation was high, and in this sample of early adopters with limited follow-up time, we found no evidence that extended-release buprenorphine offered a retention advantage compared to other MOUD in real-world settings. Retention continues to represent a major obstacle to treatment effectiveness, and interventions are needed to address this challenge even as new MOUD formulations become available.